The innomediary role of University in shaping the start-up ecosystem - Quero-Gervilla, María José (My University, 2019)
Start-up companies are increasingly growing by exploiting disruptive ideas and recent digital technologies. As of November 2018, there are about 9,000 innovative start-ups in Italy, leading the employment rate to grow up above 5% per semester, with about 40,000 shareholders and over 12,000 employees (Sole 24 Ore, 2018). Many scholars investigated the growing phenomenon of start-ups in last decade (Petretto, 2009; Blank, 2013; Cohen et al., 2019) highlighting the most relevant features as the drivers of success (Scagnelli et al., 2018), the control systems (Samagaio et al., 2018) and the role of actors in shaping the start-up ecosystem (Sipola et al., 2016). Multiple actors participate in start-up ecosystems by integrating their resources and competences (Krajcik and Formanek 2015): start-uppers, policy makers, venture capitalists and other risk capital providers, as well as incubators and accelerators. In detail, start-up business incubators are structures designed to stimulate and support the birth of new business activities through the offer of physical resources, logistics services, active managerial assistance, access to privileged financing channels and support in the use of technical services (Boschetti 2003). Some of the advantages brought by accelerators have been investigated by scholars (Kanbach and Stubner, 2016) and categorized as a focus wider than the business idea itself such as the involvement of equity, the support during the venture stage, and overall help in organizing business activities. Among accelerators an interesting role is performed by universities. However, it is a quite new phenomenon, still unexplored, further research has been called for (Colombo et al., 2018). Most of studies indeed focus on the relationship between universities and young companies in term of spin-offs, education/training activities and technology transfer (Shane, 2003, Petretto, 2009; Dempwolf et al., 2014). Due to the novelty of these supports,
Keywords: Nuevas empresas-Crecimiento; Innovation; Strat-up; Innomediary; Service Dominant Logic